Tinjauan Pustaka: Inovasi Formulasi Tablet Lepas Lambat Untuk Meningkatkan Kepatuhan Pasien - Reski Mulia; Muhammad Fathurrahman (LPPM Institut Pendidikan Nusantara Global, 2025)
Patient adherence to medication regimens is a crucial determinant of therapeutic success. Poor adherence remains one of the major causes of treatment failure, particularly in long-term therapies that require consistent and repeated drug administration. One effective pharmaceutical strategy to enhance patient compliance is the development of sustained-release drug delivery systems. These systems are designed to release active pharmaceutical ingredients gradually over an extended period, thereby maintaining therapeutic drug concentrations in the bloodstream while reducing dosing frequency. This systematic review aims to analyze recent innovations in sustained-release tablet formulations developed over the past decade and to evaluate their contribution to improving patient adherence. Literature searches were conducted across major scientific databases, including PubMed, ScienceDirect, and Google Scholar, covering publications from 2015 to 2025. The search employed the following keywords: “sustained release tablet,” “controlled release formulation,” “patient compliance,” and “pharmaceutical innovation.” A total of 32 articles met the inclusion criteria after rigorous screening and evaluation. The analysis revealed substantial advancements in formulation technology, particularly through the application of both natural and synthetic polymers such as hydroxypropyl methylcellulose (HPMC), carbopol, and chitosan. Furthermore, the integration of modern technologies—including 3D printing, matrix systems, and osmotic pump mechanisms—has significantly enhanced drug release efficiency, prolonged therapeutic duration, and minimized dosing frequency. Overall, sustained-release tablet formulations play a pivotal role in improving patient adherence, especially in chronic treatments, and continue to evolve alongside modern pharmaceutical innovations.